Social anxiety disorder and the psychobiology of self-consciousness - Stein, Dan J. (Frontiers in Human Neuroscience, 2015)
Individuals with social anxiety disorder (SAD) are characterized by fear or anxiety about social situations, but also by important alterations in self-referential processing. Given advances in our understanding of the neurocircuitry and neurochemistry of SAD, the question arises of the relationship between this research and an emergent literature on the psychobiology of self and self-consciousness. A number of investigations of SAD have highlighted altered activity in the medial prefrontal cortex (involved in self-representation), insula (involved in interoceptive processing), and other structures that play a role in bodily self-consciousness, as well as the potential value of interventions such as selective serotonin reuptake inhibitors and self-focused reappraisal in normalizing such changes. Future studies to more closely investigate associations between psychobiological alterations and changes in self-related processing in SAD, may be useful in shedding additional light on both SAD and self-consciousness.